Entre as folias do São Francisco: de uma Geografia da religião a uma Geografia da religiosidade popular no norte de Minas Gerais - Borges, Maristela Corrêa (2015)
Thinking about how different human sciences recognize the importance of religion in their studies and research, and in the way that the geography, from its beginnings, has approached this subject, rarely understanding it as important and revealing to the human action in space, I traced the first objective of this thesis. I try to understand the theoretical pathways through which geography went to pour in geography of religion. For this, I analyze separately the development of scientific studies on religion, and I try to rescue on the history of geographical thought, the closest time to a beginning of geography of religion. From brief analyzes and dialogues with theses and dissertations about geography of religion in Brazil, I try to understand how this field has developed, what s its weaknesses and its potential. Reflecting on my work as a researcher in traditional communities in the riverside area of the river São Francisco, in the north of Minas Gerais, I realized how much the popular religiosity acts significantly among its residents. Thus, I tried to recover and analyze the role of popular catholicism, from one of its present manifestations in these communities - the Folias. Through different analyzes I would like to present the Folias while a religious identity with a role that has two dimensions: the religious, that contributes significantly in the redefinition of a traditionalism of these communities; and the geographical, that the various relationships established with different spaces, are characterized as one of the popular religious manifestations with the greatest potential for studies and research on the geography of religion.